Expression and function of the inhibitory Fcγ-receptor in CIDP. - Nimmerjahn, Falk; Lünemann, Jan D. (Journal of the Peripheral Nervous System, 2011)
The inhibitory Fc-gamma receptor (FcγR) IIB, expressed on myeloid and B cells, has a critical role in the balance of tolerance and auto-immunity, and is required for the anti-inflammatory activity of intravenous immunoglobulin (IVIg) in various murine disease models. We found that treatment-naÏve patients with chronic inflammatory demyelinating polyneuropathy (CIDP) showed an impaired expression of FcγIIB levels on naÏve B cells, and failed to upregulate or to maintain upregulation of FcγIIB, as B cells progressed from the naÏve to the memory compartment. The impaired expression of FcγRIIB was, at least partially, restored by clinically effective IVIg treatment. It remains to be determined whether FcγRIIB expression is a candidate for pre-treatment assessment and might thus be used as a prognostic marker of treatment response to IVIg. Nonetheless, our data suggest that new strategies specifically targeting FcγRIIB expression might have therapeutic merit in CIDP.